Letter to Leona Strickland from Dugald Hudson, November 27, 1944 - Hudson, Dugald (Valdosta State University Archives and Special Collections, 1944)
Letter to Leona Strickland from Dugald Hudson, November 27, 1944 To: Strickland, Leona (Valdosta, GA) From: Hudson, Dugald Description: Dugald is living in a richly furnished home previously occupied by the local leader of the Nazi party. Dugald enjoys hearing about Leona’s activities and wishes he could be there. Original Label: 17
1 Electronic record(s) and derivatives. `hudson_letter_1652.pdf` 2 pages. 1432460 bytes. MD5: 8FE5CB035D14DDBB9EDFF0ED9AA450AA
Keywords: Hudson, Dugald; Hudson, Leona